Estudo comparativo de argamassas de revestimento com incorporação de resíduo de borracha de pneus inservíveis em comparação com argamassas com aditivo incorporador de ar - Philippsen, Cristiane (Universidade do Vale do Rio dos Sinos, 2020)
Nowadays, the waste from scrap tires has received special attention due to the environmental policies, which determined that the responsibility for their disposal must be from the tire industry and the tire importing companies. In Brazil, 730,000 tons of tires were placed on the aftermarket in 2016 and 494,000 tons were properly disposed. The large volume of tires produced and discarded, as well as the prospect of growth in the automotive sector, justify the efforts made in research, with the purpose of developing applications and alternatives for the use and recovery of rubber from used tires. On the other hand, the construction industry is a large consumer of non-renewable natural resources, so its use in this sector can bring economic and environmental benefits. This study consists in the analogy between the properties of mortars containing rubber from scrap tires in its composition, with a mortar containing air-entraining additive. The mortars with partial replacement of sand by rubber aggregate were produced in the percentages 0%, 2%, 4% and 6%, as well as mortars with air incorporating additive that have similarity in density with rubber mortars previously mentioned, on proportion of 1: 1: 6 (cement, lime and sand) by volume. The results showed that the rubberized mortars have similar behavior to air-entraining additive mortars, with some advantages. Water absorption by capillarity and shrinkage are lower in rubber mortars, so the use of this material can be beneficial in preventing cracking.
Keywords: Argamassa; Resíduo de borracha; Aditivo; Ar incorporado; Mortar; Scrap tire; Air-entraining additive; ACCNPQ::Engenharias::Engenharia Civil